Tooth Canal Working Length Electric Meter - Virbalis, Juozapas Arvydas; Kelbauskas, Eduardas; Martinaitis, Jonas; Rybakov, Aleksandr; Marciulionis, Povilas; Lukocius, Robertas; Urniezius, Renaldas; Otas, Konstantinas (Elektronika ir Elektrotechnika, 2015)
Electrical apical constriction locators are not harmful for humans and allow to measure exactly the physiological apex of tooth root canal. The original apex locator measurement circuit is presented. It has the power supply sources of low and high frequencies. Each measurement cycle consists of three measurement intervals. The dependence of measurement accuracy on capacitance between the electrodes and other canal electric properties is eliminated. The analysis of measurement circuit is performed. The results of experimental investigation are presented. The apical constriction is found reliably and exactly. DOI: http://dx.doi.org/10.5755/j01.eee.21.3.5901